PERAN GENERASI MUDA SEBAGAI GARAM DAN TERANG DUNIA DALAM PERSPEKTIF: MATIUS 5:13-16 - suhendra, Suhendra; Laoli, Mei Sehati; Suhartono, Gracia Vania (JURNAL TABGHA, 2025)
This study aims to examine the role of Christian youth as the salt and light of the world based on Matthew 5:13-6 in the context of contemporary life. Today’s young generation faces significant challenges, including instant lifestyles, digital disruption, and moral crises. Employing a descriptive method and contextual approach, this research integrates theological interpretation with social data and youth delinquency statistics to construct a relevant and applicable understanding. The findings reveal that Jesus’ call to be the salt and light of the world remains deeply relevant, especially in shaping the character, communication, spirituality, and ethical conduct of millennials and Gen Z. This study contributes to practical theology and the spiritual formation of youth in modern times.